Comparison of the efficacy of PFNA and InterTAN intramedullary nail in the treatment of unstable intertrochanteric femoral fractures in the elderly - Fenghui Feng (Frontiers in Medicine, 2025)
PurposeTo compare clinical outcomes between Proximal Femoral Nail Anti-rotation (PFNA) and InterTAN intramedullary nail system in treating unstable intertrochanteric femoral fractures (IFF) in elderly patients.MethodsA retrospective study of 381 patients with IFF at Tianjin Third Central Hospital compared PFNA (n = 189) and InterTAN (n = 192) surgical treatments. Patient demographics, surgical parameters, postoperative outcomes, Visual Analog Scale (VAS) pain scores, and Harris hip scores were analyzed. Follow-up lasted 6–9 months through outpatient visits and telephone calls.ResultsBoth groups showed comparable baseline characteristics including age, gender, affected side, injury mechanism, comorbidities, and Tronzo-Evans classification (P > 0.05). The PFNA group demonstrated clinically meaningful shorter operation times and reduced blood loss compared to InterTAN (P < 0.05). The InterTAN group achieved earlier postoperative weight-bearing (P < 0.05). No significant differences were found in hospitalization duration or intraoperative blood transfusion rates (P > 0.05). Pain scores were lower in the InterTAN group during the early postoperative period (P < 0.05). Harris hip scores were superior in the InterTAN group during the first week and month post-surgery (P < 0.05), but showed no significant differences at 3 and 6 months (P > 0.05). Postoperative complication rates were similar between groups (P > 0.05).ConclusionWhile both techniques demonstrated comparable long-term outcomes, PFNA may offer advantages in surgical efficiency and blood loss reduction, whereas InterTAN showed improved early postoperative outcomes regarding weight-bearing and initial pain management. The choice between techniques should consider patient-specific factors and surgical priorities. Further prospective studies are warranted to establish stronger clinical guidance.